Language as an Error: A Study on School Literacy and Language Correction in Lithuania - Vaicekauskienė, Loreta; Vukotić, Vuk; Čičirkaitė, Ramunė; Nevinskaitė, Laima (Taikomoji kalbotyra, 2022)
This special issue documents the history of formal writing education in Lithuania in the second half of the 20th and early 21st centuries by taking a (socio)linguistically informed approach to school literacy. The study consists of four contributions, one theoretical and three empirical. The authors explore authentic pupils’ written language practices by focusing on variation in spelling, morphology and syntax, word choice as well as stylistic expression, as corrected by teachers, and critically contrast the data with the dominant normativist (or prescriptivist) approach to school literacy in Lithuania. The data for the empirical contributions were retrieved from an anonymised database “Rašinėliai” (‘School Essays’) which some of the authors of the study have been collecting since 2014 for the purpose of investigation of school writing in Lithuania. At the time the study was conducted, the researchers could choose among more than 7,500 PDF files documenting writing by almost 950 different pupils between 1st and 12th grades, of which almost 80% were teacher-corrected. The results of the study can be interpreted as revealing the cognitive and social diversity of the literacy phenomenon. There were virtually no cases in the data of the pupils’ written essays that could not be explained by natural cognitive or social causes. Among the main causes of linguistic variation, the findings identified (1) the influence of spoken language with its own phonetic and grammatical rules; (2) the cognitive mechanism called analogy, whereby pupils internalise a certain spelling convention and then generalise it; and (3) the potentially interconnected factors as the genre, the motivation of the pupils and pedagogical practice. The authors hope that the study will show both the originality and productiveness of the sociolinguistic approach when applied to data from Lithuanian schools, as well as its theoretical potential of developing sociolinguistics of school literacy. Besides that, there is an expectation that the research will have important implications for local educational policies and pedagogical practice.
Keywords: teaching of writing; language variation; prescriptive writing pedagogy; language correction practice